Herodium and Southeastern Judea in the Great Revolt and the Bar Kokhba Revolt: A Comparative Viewpoint - Porat, Roi ca. 20./21. Jh. (Zeitschrift des Deutschen Palästina-Vereins, 2023)
The fortified structure that King Herod built atop Mount Herodium, which is located south of Jerusalem on the edge of the Judean Desert, served the Jewish rebels between the two revolts against the Romans in the l " and 2nd cent. C.E. According to Josephus, in the Great Revolt the site served as a stronghold of the rebels, apparently Idumaean 1, who held it from 66 C.E. to the Roman takeover in 71 C.E. The Wiidi Murabba'iit documents show that in the Bar Kokhba Revolt (132-136 C.E.) the fortress served as a headquarters and an administrative center of the Bar Kokbha state. These facts, together with the wealth of archaeological findings discovered at Herodium and the "cave shelters" established in the surrounding desert, as well as a study of the site in its geographicalphysical context, reveals the strategic importance of Herodium in southeastern Judea, and the key nature of the site in studying the rebellions in Judea. Yet the picture that emerges from the study of Herodium shows its very different significance in each revolt. This article presents a comparison between the two rebellions from a variety of standpoints that have been discussed separately in previous studies 2. It offers a synthesis - a comparison of all possible data and insights that have emerged so far, analyzing the local and regional significances and suggesting ways to understand them. In terms of Herodium's function in the region, this article shows that in the Great Revolt, the fortress served as a buffer between the mountains and the desert, and was apparently intended to protect the adjacent Idumaean settlement area. In contrast, during the Bar Kokhba Revolt, Herodium was a kind of bridge and base that connected the regions of the revolt in the Judean Desert, in Judea and in Idumaea. The article proposes that these differences stemmed mainly from the military and civilian interests of the rebels in each instance as well as the condition of the leadership, which was split in the Great Revolt and unified in the Bar Kokhba Revolt.